INTELLIGENT OUTDOOR PARKING SPOT LOCATOR - Lo, Lemuel Li Yong (Universiti Malaysia Sarawak (UNIMAS), 2019)
The drivers always waste time looking for a parking slot especially when in a rush. The drivers need to search the entire area to find an available parking slot to park their cars. This issue has been causing inconvenience to the car drivers. It also consumes a lot of time and wastes petrol. The objective of the system is to detect the available parking slots in real-time. The parking sensor will detect the available parking slots, it provides real-time information on the status of parking slots. In addition, it also displays available parking slots to drivers. The webpage or mobile application will display parking status to drivers. It helps drivers find available parking slots faster and more comfortably. Moreover, it also collects the occupancy of the parking slots. The parking sensor will detect the car in the parking slot and send the signal to microcontroller, and then the microcontroller will send the data to the 000webhost via Wi-Fi. Unfortunately, this system can help more of the drivers to solve the parking problem. The system develops by some technologies and tools such as PHP develop the website, Java programming to build mobile application and Arduino code for detect from hardware.